The - Wallace, Mary (Owl Books, 1999)
The image of a traditional Inuit stone structure, or inuksuk, silouetted against an arctic sky, has become a familiar symbol. Yet, for many, their purpose remains a mystery. In a stunning new book, artist and children's author Mary Wallace, in consultation with Inuit elders and other noted experts, gives a fascinating introduction in words, pictures, and paintings to the many forms of the inuksuk structure and its unique place in Inuit life and culture